Stock Market Reaction to the Tax Amnesty Announcement - Wibowo, Muhammad Satriyo; Sukmaningrum, Puji Sucia (UI Scholars Hub, 2019)
The Indonesian Government has put in place policies that are quite bold and that highly impacton both companies and the economy. This includes the endorsement tax amnesty policy in 2016.This study aims to investigate the reaction of the stock market against the policy. The dataset of this research was 100 companies listed on the Indonesian Islamic Stock Index (ISSI). Research methods used the event study market adjusted model to look at changes in the Average Abnormal Return (AAR) and Trading Volume Activity (TVA) during the announcement. The results of this research show there is a difference in the AAR and TVA before and after the announcement. The investors positively viewed the information content of the tax amnesty policy. The government has made a very good policy and it supports the improvement in the quality of corporate governance and company performance.